Visitation Modality Preferences for Adults Visiting Jails. - Tartaro, Christine; Levy, Marissa P. (Prison Journal, 2017)
The development of technology has introduced new options for prison and jail visits, including video visits from jail lobbies and remote video from virtually anywhere. Researchers surveyed visitors to three jails who were participating in either on-site visits through Plexiglas, lobby video visits, or remote video visits. On-site Plexiglas visitors rated their visits as more stressful and time-consuming, while remote video visitors were most likely to indicate that it was difficult to locate finances for the visit. Visitors expressed a preference for contact visits but noted that remote video visits were likely to be the most convenient.